National Gallery Technical Bulletin (London). (Londen : National Gallery (Londen), 1977)
The National Gallery Technical Bulletin, first published in 1977, has achieved a leading position in the study of the materials and techniques of painting, and the scientific examination of paintings. Published annually, it is essential reading for conservators, conservation scientists, art historians, collectors and curators.Drawing on the combined expertise of curators, scientists and conservators, it brings together a wealth of information about artists materials, practices and techniques. (https://www.nationalgallery.org.uk/research/research-resources/technical-bulletin)
Online: https://www.nationalgallery.org.uk/technical-bulletin/technical-bulletin-volume-index
Engels
Tijdschriften
Keywords: techniek